Campaign Spending Limits and Political Advertising - Soberman, David; Sadoulet, Loïc (Management Science, 2007)
Traditionally, research on political campaigns has focused on the positioning of parties and not on how parties communicate with the electorate. We construct a model where two parties fund both the “creative” and “media” elements of political advertising and examine how campaign budgets affect advertising strategies in the context of a political campaign. Our key finding is that tight campaign limits stimulate aggressive advertising on the part of competing parties, while generous budgets often lead to parties acting defensively. The analysis also provides an explanation for the increasingly partisan campaigns that the Republicans and Democrats have taken in recent elections. When there is significant polarization amongst noncommitted voters and campaign spending limits are higher, we find that parties “retrench” toward traditional constituencies.